Estimating reserve lipids in greater scaup ( Aythya marila ) and lesser scaup ( A . affinis ) - Chappell, William A.; Titman, Rodger D. (Canadian Journal of Zoology, 1983)
Greater scaup (Aythya marila) and lesser scaup (A. affinis) were collected during their spring and fall migrations at Lake St. Louis, Quebec, in 1979 and 1980. Body measurements and weights of fat deposits were obtained for 35 greater scaup and 39 lesser scaup. Carcasses were homogenized and analyzed for lipid and water content. Percent body water and skin weight were the best predictors of ether-extractable body lipids. Body weight and body weight/body length were good predictors of ether-extractable lipids but may provide less reliable estimates if used for scaup at other stages of their annual cycle. Only abdominal fat weight could be used to derive a single predictive equation estimating ether-extractable lipids for both species. Regression lines with body weight or body weight/body length as the independent variables had the same slope for both species but these differed in elevation.